2019
DOI: 10.2147/cmar.s193948
|View full text |Cite
|
Sign up to set email alerts
|

<p>Safety and efficacy assessment of transarterial chemoembolization using drug-eluting beads in patients with hepatocellular carcinoma and arterioportal shunt: a single-center experience</p>

Abstract: Objective To evaluate the feasibility and safety of transarterial chemoembolization with drug-eluting beads (DEB-TACE) in patients with hepatocellular carcinoma (HCC) and arterioportal shunts (APSs). Materials and methods Fifty-eight patients with unresectable HCC and APSs who were treated with DEB-TACE (n=26) or polyvinyl alcohol (PVA) plus TACE (PVA-TACE, n=32) were included in this retrospective study. The tumor response was evaluated by the modified Response Evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 26 publications
(33 reference statements)
3
14
0
Order By: Relevance
“…Although these were not head-to-head comparisons, it could still be concluded that combination therapy of DEB-TACE and apatinib provided a relative and clinically meaningful improvement in OS and PFS over DEB-TACE alone or apatinib monotherapy. In the present study, we found that the median OS was longer than that of DEB-TACE monotherapy as reported by Xiao YD et al (22.0 months vs 11.5 months) (19). A slight advantage of survival time can be seen in our study when compared to that of Zhen L's study (13 months) (7).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Although these were not head-to-head comparisons, it could still be concluded that combination therapy of DEB-TACE and apatinib provided a relative and clinically meaningful improvement in OS and PFS over DEB-TACE alone or apatinib monotherapy. In the present study, we found that the median OS was longer than that of DEB-TACE monotherapy as reported by Xiao YD et al (22.0 months vs 11.5 months) (19). A slight advantage of survival time can be seen in our study when compared to that of Zhen L's study (13 months) (7).…”
Section: Discussionsupporting
confidence: 73%
“…In the current study, the liver function of patients deteriorated at first week after therapy and recovered at 1 month after the procedure. Compared to previous studies that focused on conventional TACE, the liver damage in our study was relatively less severe (18,19). Although this combination therapy achieved promising efficacy in the treatment of HCC, it is also illustrated some adverse reactions.…”
Section: Discussionmentioning
confidence: 51%
“…In the present meta-analysis, we initially searched formally published studies to comprehensively compare the efficacy and safety of CSM-TACE with that of cTACE for treating HCC patients. A total of 16 studies and 1,454 patients with HCC were included, of whom 722 were treated with CSM-TACE and 732 were treated with cTACE (14)(15)(16)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). CR, ORR, DCR, PFS, OS, adverse events and liver function indexes were compared and analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…This is presumably because of the presence of a hepatic APS in iHCC, which intra-arterial lipiodol will pass through into the portal vein, resulting in poor deposition in the tumor area [23]. Because DEB has the property of sustained tumor-selective drug delivery and permanent embolization of tumor-feeding vessels, we believe that DEB is more appropriate than lipiodol for patients with iHCC and APS [2426].…”
Section: Discussionmentioning
confidence: 99%